2012
DOI: 10.1371/journal.pone.0035882
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Dicer in Smooth Muscle Affects Voiding Pattern and Reduces Detrusor Contractility and Neuroeffector Transmission

Abstract: MicroRNAs have emerged as important regulators of smooth muscle phenotype and may play important roles in pathogenesis of various smooth muscle related disease states. The aim of this study was to investigate the role of miRNAs for urinary bladder function. We used an inducible and smooth muscle specific Dicer knockout (KO) mouse which resulted in significantly reduced levels of miRNAs, including miR-145, miR-143, miR-22, miR125b-5p and miR-27a, from detrusor preparations without mucosa. Deletion of Dicer resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
(62 reference statements)
4
40
1
Order By: Relevance
“…Using the same mouse model, we also demonstrated impaired depolarizationinduced contraction in the urinary bladder (32). Expression of smooth muscle differentiation markers was, however, hardly affected in the bladder, contrasting with our findings in the aorta.…”
contrasting
confidence: 95%
See 2 more Smart Citations
“…Using the same mouse model, we also demonstrated impaired depolarizationinduced contraction in the urinary bladder (32). Expression of smooth muscle differentiation markers was, however, hardly affected in the bladder, contrasting with our findings in the aorta.…”
contrasting
confidence: 95%
“…Aorta and bladder were excised, cleaned, and quickly frozen in liquid nitrogen. The samples were homogenized in SDS sample buffer (60 mM Tris·HCl pH 6.8, 2% SDS, and 10% glycerol) as previously described (32). The amount of protein was determined using Bio-Rad DC protein assay.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Frozen tissue was pulverized using liquid nitrogen as described previously (30). Proteins were detected using commercially available primary antibodies: ␣-actin (1:2000; Sigma-Aldrich, catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…The comparative analysis of the miRNA expression profiles in BPS, bladder cancer, and several inflammatory disorders showed that seven of 31 miRNAs altered in BPS had the same regulatory pattern in inflammatory bowel disease (11), which shares many features with BPS (12). Recently, the role of miRNAs in the bladder smooth muscle was investigated using an induced smooth muscle-specific Dicer knock-out, which caused a significant reduction of miRNA levels, including miR-145, miR-143, miR-22, miR-125b-5p, and miR-27a, leading to a disturbed micturition pattern in vivo (13). In a similar study, the loss of Dicer exacerbated cyclophosphamide-induced bladder overactivity in mice (14).…”
mentioning
confidence: 99%